2022
DOI: 10.3390/pharmaceutics14071446
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of CYP2D6 Phenotypes on the Pharmacokinetics of Propafenone: A Systematic Review and Meta-Analysis

Abstract: Propafenone (PPF) is a class 1C antiarrhythmic agent mainly metabolized by cytochrome (CYP) 2D6, CYP1A2, and CYP3A4. Previous studies have shown that CYP2D6 polymorphism influences the pharmacokinetics (PK) of PPF. However, the small sample sizes of PK studies can lead to less precise estimates of the PK parameters. Thus, this meta-analysis was performed to merge all current PK studies of PPF to determine the effects of the CYP2D6 phenotype more accurately on the PPF PK profile. We searched electronic database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The diagnosis of poisoning should be based on the observed effects on the human body, as well as the determination of whether the concentration of the xenobiotic in the blood is therapeutic, toxic or lethal. For a single oral therapeutic dose of PPF of 300-400 mg, the plasma concentrations ranged from 0.3 to 1.4 µg/mL [7]. At an oral dose of 150 mg every 6 h with a 4-day duration of administration, the reported steady state plasma concentration was up to 0.45 µg/mL [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of poisoning should be based on the observed effects on the human body, as well as the determination of whether the concentration of the xenobiotic in the blood is therapeutic, toxic or lethal. For a single oral therapeutic dose of PPF of 300-400 mg, the plasma concentrations ranged from 0.3 to 1.4 µg/mL [7]. At an oral dose of 150 mg every 6 h with a 4-day duration of administration, the reported steady state plasma concentration was up to 0.45 µg/mL [33].…”
Section: Discussionmentioning
confidence: 99%
“…PPF from a sustained-release tablet persists in the body longer and at a lower concentration, which ensures milder adverse effects. Several studies have shown that at therapeutic doses, poor metabolizers experience a significantly higher PPF concentration and elimination half-life [7]; thus, at therapeutic doses, which can become toxic, various adverse effects are observed. Zhender et al [8] observed nausea and vomiting at short-term higher therapeutic doses and the exacerbation of ventricular extrasystoles during long-term treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is noteworthy that these pharmacokinetic variations predominantly manifest as differences in heart rate, as opposed to other response phenotypes such as hypertension [32,33]. Various studies -including those by Thomas and Johnson [30] and Cunningham and Chapman [34] -have underscored this distinction. Within this domain, polymorphisms in the β adrenergic receptors ADRB1 and ADRB2, as well as in the G protein-coupled receptor kinase 5 gene GRK5 and G protein subunit beta 3 gene GNB3, have emerged as significant contributors [31,35].…”
Section: β-Blockersmentioning
confidence: 99%
“…[12] Section 2), but further mechanistic insight is needed. Propafenone, an antiarrhythmic drug, is also mentioned by the FDA as a potential risk for adverse events among CYP2D6 PMs, although there is not yet substantial evidence of a pronounced influence of CYP2D6 on its pharmacokinetic properties [30]. An overview of the polymorphic metabolism and transport as well as the effect of statins and P2Y1 / P2Y2 inhibitors is provided in Figs.…”
Section: Most Important Polymorphic Genes In the Drug Treatment Of Ca...mentioning
confidence: 99%